The Effectiveness of Direct Learning: A Comprehensive Review in the Context of Educational Psychology - Junita Sipahelut; Munaisra Tri Tirtaningsih; Ika Andrini Farida (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Abstract: The purpose of this article is to conduct an evaluation review of the effectiveness of using direct instruction in educational psychology. In this review, the author analyzes various aspects ranging from the underlying theory, application, and influence on student learning outcomes and motivation. This study uses a comprehensive literature review method, with data taken from various sources such as journal articles, textbooks, and other related publications. The results of the study show that direct instruction is quite effective in improving student learning outcomes, especially in subjects that are structured and skill-based. This approach can increase the efficiency of the learning process, provide students with a program-like structure, and enable them to master the material gradually. However, the effectiveness of direct instruction tends to vary depending on student characteristics, subject type, and the quality of the method's implementation. Keywords: Direct Instruction, Learning Outcomes, Motivation, Learning Strategies. Abstrak: Tujuan dari artikel ini adalah untuk melakukan review evaluasi tentang efektivitas penggunaan pembelajaran langsung dalam psikologi pendidikan. Dalam review, penulis menganalisis beragam aspek mulai dari teoretis yang mendasari, penerapan, dan pengaruh terhadap hasil serta motivasi belajar siswa. Penelitian ini menggunakan metode kajian literatur secara menyeluruh, data diambil dari berbagai sumber seperti artikel jurnal, buku teks, dan publikasi-publikasi lain berkaitan. Hasil kajian menunjukkan bahwa pembelajaran langsung cukup efektif dalam meningkatkan hasil belajar siswa, khususnya pada mata pelajaran yang strukturnya terorganisir dan berdasarkan keterampilan. Pendekatan ini mampu meningkatkan efisiensi proses belajar, memberikan struktur bersifat program kepada siswa, serta memungkinkan mereka untuk menguasai materi secara bertahap. Meskipun, efektivitas pembelajaran langsung cenderung bervariasi bergantung kepada karakteristik siswa, jenis mata pelajaran, dan pada kualitas pelaksanaan metode tersebut. Kata kunci : Pembelajaran Langsung, Hasil Belajar, Motivasi, Strategi Pembelajaran.